PENDEKATAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR DAN AKTIFITAS PEMBELAJARAN MATEMATIKA SISWA KELAS IX SMPN 1 KARANGPLOSO - Erna Yuni Hartati (Center of Language and Cultural Studies, 2018)
This study examines how cooperative learning using STAD improves attainment and students classroom activities in learning math. This study used classroom actions research with three cycles and involved 32 ninth graders of SMPN 1 Karangploso Malang. The results evidently show that scores increase from cycle to cycle and so do the learning activities. Respectively, scores achieving minimum achievement (KKM) from cycle I, cycle II, and cycle III are 18.75%, 68.75%, and 81.24%. Similarly, classroom activities identified with the mean percentage increase from cycle to cycle as follows: 60.94%, 74.48%, and 84,42%. It implies that STAD, in particular, is effective in teaching math and other lessons for SMP, provided indicators to evaluate learning activities are based on the criteria used in this study.